A wood-rot fungus-mediated production of isobutylene from isobutanol. (1st October 2019) - Kim, Do-Hyung; Lee, Doo-Geun; Park, JongKee; Yang, Yung-Hun; Park, Jeong-Hoon; Yoon, Jeong-Jun
Graphical abstract: Abstract: Generally, isobutylene is produced by petroleum-derived chemical processes, but manufacturing methods using renewable sources, such as biomass, have been considered because of limited amounts of fossil fuel and environmental issues. In this study, isobutylene was converted from isobutanol through dehydration by hydrogen ions generated from oxalic acid and the Fenton reaction during the fermentation of wood-rot fungus, Fomitopsis palustris . The formation of isobutylene from isobutanol was confirmed by in vitro reactions simulating the Fenton reaction caused by F. palustris . The maximum production rate of isobutylene was 34.7 nmol h −1  gcell −1 . This was approximately 5.9 times higher than that of a previous study of isobutylene production by Saccharomyces cerevisiae mevalonate diphosphate. Unlike previous biological production studies of isobutylene, our findings showed that isobutylene was converted through the dehydration of isobutanol during fermentation of F. palustris .